Institutional COVID-19 Protocols: Focused on Preparation, Safety, and Care Consolidation. Issue 4 (October 2020) - DiSilvio, Briana; Virani, Ahmed; Patel, Samir; Finoli, Lauren; Singh, Anil; DuMont, Tiffany; Cheema, Tariq
Abstract : As the confirmed cases of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) continue to grow with over 1 million documented infections in the United States alone, researchers and health care workers race to find effective treatment options for this potentially fatal disease. Mortality remains high in patients whose disease course requires mechanical ventilation and admission to intensive care units. While focusing on therapies to decrease mortality is essential, we must also consider the logistical hurdles faced with regard to safely and effectively delivering treatment while limiting the risk of harm to hospital staff and other noninfected patients. In this article, we discuss aspects of surge planning, considerations in limiting health care worker exposure, the logistics of medication delivery in a uniform and consolidated manner, protocols for delivering emergent care in a rapidly deteriorating coronavirus disease-2019 (COVID-19) patient, and safe practices for transporting infected patients.